Pengaruh Tingkat Suku Bunga dan Jumlah Uang Beredar terhadap Investasi dan Pertumbuhan Ekonomi Indonesia - Sudirman Sudirman; Nurul Hidayat A; Abdul Rahman (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This study aims to determine the effect of interest rates, the money supply on economic growth in Indonesia through investment. The type of data used is secondary data (time series) for the quarter period for the last nine years, namely from 2015-2020. Data were obtained from the Central Statistics Agency (BPS) and Bank Indonesia (BI), as well as other sources. The data analysis method is path analysis (using SPSS version 26 software. The results show that, directly, interest rates and money supply have no significant effect on investment. However, interest rates and money supply have a significant effect on economic growth in Indonesia, meanwhile investment has no significant effect on economic growth in Indonesia. Then, indirectly, interest rates and the money supply have an effect on economic growth through investment.